The firm-level link between productivity dispersion and wage inequality: A symptom of low job mobility? - Criscuolo, Chiara (OECD Economics Department Working Papers, 2021)
Differences in average wages across firms - which account for around one-half of overall wage inequality - are mainly explained by differences in firm wage premia (the part of wages that depends exclusively on characteristics of firms) rather than workforce composition. Using a new cross-country dataset of linked employer-employee data, this paper investigates the role of cross-firm dispersion in productivity in explaining dispersion in firm wage premia, as well as the factors shaping the link between productivity and wages at the firm level. The results suggest that around 15% of cross-firm differences in productivity are passed on to differences in firm wage premia. The degree of pass-through is systematically larger in countries and industries with more limited job mobility, where low-productivity firms can afford to pay lower wage premia relative to high-productivity ones without a substantial fraction of workers quitting their jobs. Stronger product market competition raises pass-through while more centralised bargaining and higher minimum wages constrain firm-level wage setting at any given level of productivity dispersion. From a policy perspective, the results suggest that the key priority should be to promote job mobility, which would reduce wage differences between firms while easing the efficient reallocation of workers across them